Diseño del sistema hidráulico para las redes de tuberías para el agua de proceso, tratada, lluvia y de emergencia del centro de procesos e innovación para la industria sostenible de la Fundación Universidad de América (2022)
The Center for Processes and Innovation for Sustainable Industry (CEPIIS) plant comprises a building focused on scientific research, developed by the University of America with the specific objective of offering students the necessary technological tools to develop learning skills and a Approach to the application of the acquired knowledge. Within this document, an exhaustive review of the regulations for pipe networks in Colombia is evidenced, with which the specific requirements of each network are defined. The diameters for each of the networks were determined and their respective commercial equivalence was chosen, then the load losses per surface and per accessories were calculated with which the respective pumps were selected; For this, the system curve was made for each of the networks, which were compared with the characteristic curves of the pumps to establish their operating point.